2011
DOI: 10.1016/j.jecp.2010.08.012
|View full text |Cite
|
Sign up to set email alerts
|

A brighter side to memory illusions: False memories prime children’s and adults’ insight-based problem solving

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract Can false memories have a positive consequence on human cognition? In two experiments we investigated whether false memories could prime insight problem-solving tasks. Children and adults were asked to solve compound remote associate task (CRAT) problems, half of which had been primed by the presentation of Deese/Roediger-McDermott (DRM) lists whose critical lure was also the solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 31 publications
10
80
0
2
Order By: Relevance
“…Howe et al (2010a) demonstrated that adult participants solved more CRATs more quickly when primed with a false memory than when no prime was presented. This finding has been replicated and extended to include priming in children (Howe, Garner, Charlesworth & Knott, 2011).…”
Section: Priming Analogical Problem Solutionsmentioning
confidence: 59%
See 3 more Smart Citations
“…Howe et al (2010a) demonstrated that adult participants solved more CRATs more quickly when primed with a false memory than when no prime was presented. This finding has been replicated and extended to include priming in children (Howe, Garner, Charlesworth & Knott, 2011).…”
Section: Priming Analogical Problem Solutionsmentioning
confidence: 59%
“…We did, however, anticipate age and priming differences in speed of problem solving given what we know about differences in the structure of children's knowledge base (e.g., see Ceci et al, 2010;Howe, 2011b). That is, despite having the knowledge available to solve analogical problems, children's speed of processing during problem solving is thought to be slower relative to that of adults (see Howe et al, 2009Howe et al, , 2011. The question, then, was whether speed of processing could be affected by true and false memory primes in both children and adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent research typically showed the priming effect of believed false memories on CRAT problems (Howe, Garner, Charlesworth, & Knott, 2011;Howe, Wilkinson, Garner, & Ball, 2015); and found that the priming effect of false memories was similar to or even stronger than that observed for true memories (Howe, Threadgold, Norbury, Garner, & Ball, 2013;Howe, Wilkinson, Monaghan, Ball, & Garner, 2013). Based on Bernstein et al's work (2015), we predicted that if belief is more influential than recollection when it comes to impacting subsequent behaviors that ostensibly require non-conscious problem-solving processes, no priming effect would be found after beliefs for false memories are withdrawn.…”
Section: The Current Experimentsmentioning
confidence: 94%